(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The World Health Organization defines infertility as a disorder of the male or female reproductive system characterized by the inability to conceive after 12 months or more of consistent unprotected sexual activity. Secondary infertile if they have successfully became pregnant at least once in the past. 30-40% of infertility is caused by ovulatory disruption. PCOS is characterized by oligo/anovulation, excess androgen-related symptoms, and numerous ovarian cysts. Infertility correlates with Vandhyatha in Ayurveda. Acharya Harita described that failure to achieve a Praja known as Vandhayatwa. Praja is achieve by Garbha and to achieve Garbha purity of many component (Ritu, Kshetra, Ambu, Beeja) is necessary. Regarding this case, Ritu is disturbed in form of Artavkshaya, managed through principles like use of Agneya dravya, Agni Deepana, Vata Shamana and Piita Vardhna. Case presentation: A female patient, 25 years old, visited Prasuti Tantra and Stri- Roga OPD of National Institute of Ayurveda, Jaipur, on 28 august 2023 with secondary infertility associated with delayed and scanty menses for 3 years. Methodology: Detailed history with all clinical, physical examination and laboratory investigations were carried out which were normal. Ultrasonography reveals bilateral PCOD. So the treatment was planned accordingly. Patient was treated with Shatapushpa churna in 2 consecutive cycles. Result: Patient got her menstruation after one month of drug intake with improvement in menstrual pattern. She continued to take drug during the second month and missed her period consequently after that.UPT was done and was found positive